ANALISIS SOSIAL HUKUM ISLAM DALAM QS AN-NUR AYAT 22 - Mayyadah Mayyadah (Universitas Islam Negeri Alauddin Makassar, 2021)
This paper aims to analyze QS al-Nū/24: 22, from text to context. Historically, the text of QS al-Nū/24: 22came down related to the occurrence of the ḥadīṡ al-ifkī, incident that hit 'Aisyah radiyallahu 'anha. That event predicted by historians took place after the Bani Musthaliq war around 5 or 6 H. Some of the social aspects of Islamic law which contained in this text are ethical principles in social interaction, individual attitudes in dealing with slander or hoaxes, and the legal consequences stipulated by the Shari'a against perpetrators and spreaders of fake news or hoaxes.Keywords: Asbāb Nuzūl, historical context, social law, hoax.